Assessing Flood Risk Under Sea Level Rise and Extreme Sea Levels Scenarios: Application to the Ebro Delta (Spain). Issue 2 (1st February 2018) - Sayol, J. M.; Marcos, M.
Abstract: This study presents a novel methodology to estimate the impact of local sea level rise and extreme surges and waves in coastal areas under climate change scenarios. The methodology is applied to the Ebro Delta, a valuable and vulnerable low‐lying wetland located in the northwestern Mediterranean Sea. Projections of local sea level accounting for all contributions to mean sea level changes, including thermal expansion, dynamic changes, fresh water addition and glacial isostatic adjustment, have been obtained from regionalized sea level projections during the 21st century. Particular attention has been paid to the uncertainties, which have been derived from the spread of the multi‐model ensemble combined with seasonal/inter‐annual sea level variability from local tide gauge observations. Besides vertical land movements have also been integrated to estimate local relative sea level rise. On the other hand, regional projections over the Mediterranean basin of storm surges and wind‐waves have been used to evaluate changes in extreme events. The compound effects of surges and extreme waves have been quantified using their joint probability distributions. Finally, offshore sea level projections from extreme events superimposed to mean sea level have been propagated onto a high resolution digital elevation model of the study region in order to construct flood hazards maps for mid and end of the 21st century and under two different climate change scenarios. The effect of each contribution has been evaluated in terms of percentage of the area exposed to coastal hazards, which will help to design more efficient protection and adaptation measures. Key Points: A new methodology for flood hazard assessment integrating mean sea level rise and extremes under climate change scenarios is presented Sea level rise includes seasonal and inter‐annual variability, vertical land movements and joint extremes of storm surges and wind waves Offshore relative sea level rise is projected onshore by computing run‐up in order to design flood hazard maps for Ebro Delta, Spain